Effects of Employee Training and Development Programs on Corporate Financial Performance - Trirahayu, Dewi (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study explores the impact of employee training and development on corporate financial performance through qualitative inquiry. It aims to understand perceptions of training effectiveness, challenges in implementation, and the influence of organizational culture and technology. Employing a qualitative case study approach, data was gathered from employees and managers across diverse industries known for robust training programs. Semi-structured interviews, focus groups, and document analysis were used to gather and analyze data, ensuring comprehensive insights into training outcomes. Participants generally perceived training as effective in enhancing skills and productivity, aligning with literature highlighting its positive correlation with financial performance. Challenges included managerial support and resource allocation issues. Best practices identified integrating training into business strategy, employing diverse training methods, and fostering a supportive organizational culture. Technological advancements, such as e-learning, were noted to enhance training efficiency. The findings underscore the importance of strategically integrating training programs that are aligned with business goals. They suggest enhancing managerial support and resource allocation to maximize training effectiveness. Organizations benefit from cultivating a culture of continuous learning and leveraging technological tools for flexible learning environments, ultimately contributing to improved financial performance and competitiveness.